High-intensity interval training prevents muscle mass loss in overweight Chilean young adults during a hypocaloric-Mediterranean diet: a randomized trial - Monsalves-Álvarez, Matías; Jiménez, Teresa; Bunout, Daniel; Barrera, Gladys; Hirsch, Sandra; Sepúlveda-Guzman, Carlos; Silva, Claudio; Rodriguez, Juan M.; Troncoso, Rodrigo; de la Maza, María Pía (Frontiers in Nutrition, 2023)
The Hypocaloric Mediterranean diet (MD) reduces mainly fat mass, but inevitably causes a loss of skeletal muscle mass. High-intensity interval training (HIIT) seems to have advantages in preserving muscle mass during a hypocaloric regime. Our study compares body composition and metabolic changes in Chilean overweight/obese women and men after three months of weight loss treatment with a Mediterranean-type hypocaloric diet, HIIT, or a combination of both. 83 overweight or obese women and men aged 25 to 50 were enrolled in the study. The subjects were assigned randomly to one of the three intervention groups: 1) MD, 2) HIIT, and 3) MD + HIIT. Basal and after the intervention were assessed: a) Body composition by double-beam densitometry, muscle, and fat measurements by thigh Ultrasound and computed tomography, b) Muscle strength at handgrip and quadriceps, c) Exercise performance by peak oxygen consumption, peak load, work efficiency and exercise energy expenditure, and d) Metabolic parameters. Of 83 participants, the retention rate was 49% due to low compliance with the interventions. As expected, energy restriction induced significantly higher weight and fat mass loss than the other two interventions but was associated with significant loss of lean tissues, which HIIT prevented. Metabolic and glycoxidative parameters remained unchanged, irrespective of changes in body composition. Hypocaloric dieting remains the most effective means to lose weight and body fat. However, it induces lean body mass loss if not accompanied by exercise training. This study shows that HIIT prevents muscle mass loss caused by a Mediterranean hypocaloric diet.